Standardization of Midwifery Education in Efforts to Improve Professionalism in Midwifery Services in Indonesia - Kasiati, Klanting (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
-